Long-term and seasonal dynamics of zooplankton in hypergaline lake Kulundinskoye (Kulunda Steppe, Russia) - Lyubov’ V. Vesnina; Dmitry M. Bezmaternykh (Acta Biologica Sibirica, 2023)
The paper investigates the effects of natural environmental factors on the long-term (2000–2020) and seasonal (April–October) dynamics of zooplankton in the hypergaline Lake Kulundinskoye, located in the Kulunda steppe of Altai Krai, Russia. Sixteen key indicators of zooplankton structure, including abundance and biomass of major taxonomic groups such as Rotifera, Cladocera, Copepoda, and Anostraca, as well as individual stages of a life cycle and sex ratio in Artemia population, were studied in relation to 17 hydrophysical and hydrochemical indicators such as temperature, density, pH, total salinity, hardness, alkalinity, and other parameters. Monthly data for 2017–2020 and average annual data for 2000–2020 were analyzed to identify the impact of environmental factors on zooplankton structure. The study also examined the influence of these factors on the Artemia crustacean population, which dominates the zooplankton in this lake. The hydrophysical and hydrochemical regime of Lake Kulundinskoye can vary significantly from year to year, which affects the zooplankton indicators. Statistical analysis showed that monthly hydrophysical and hydrochemical data are more reliable than averaged data for the research period (April-October) in determining the impact of environmental factors on zooplankton structure. The results indicate that the changes in zooplankton structure are mainly due to the stimulating effect of increased salinity on the Artemia population and its depressing influence on other taxa. The long-term dynamics of zooplankton is characterized by a complex cyclicity of water salinity and productivity of the Artemia population, which is influenced by periodic changes in the moisture content of the lake catchment.